Pengaruh Good Corporate Government, Corporate Social Responsibility, dan Karakteristik Perusahaan terhadap Penghindaran Pajak - Elvira Kahnia Lestari; Aan Marlinah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The objective of this research is to tempt the impact of the firm size, leverage, capital intensity, independent commissioner, the audit committe, corporate social responsibility, profitability and institutional ownership to tax avoidance. Population of this research are all of manufacture companies listed in Indonesia Stock Exchange from 2017-2019. Samples are obtained through purposive sampling method, which only 75 manufacture companies that met the sampling criteria for the research. The research used multiple regression method to test the effect of each variable in influencing tax avoidance.The result of this research indicates that firm size, capital intensity and corporate cocial responsibility have an effect on tax avoidance, while leverage, independent commissioner, audit committe, institutional ownership, and profitability have no effect on tax avoidance.